Vitamin B12 (cobalamin) deficiency in gastroenterological diseases - review - Zatyka, Piotr; Opala, Dominika; Słomczyński, Adam; Pawłowska, Agata; Rabenda, Michal; Osuch, Dobromiła; Janik, Piotr (Quality in Sport, 2024)
Introduction: Vitamin B12 is a water-soluble vitamin found primarily in animal-derived products such as red meat, dairy, and eggs. An essential substance for its absorption is the intrinsic factor, produced by the parietal cells of the stomach. After absorption in the distal ileum, cobalamin acts as a coenzyme in DNA synthesis and the metabolism of fatty acids and homocysteine. In addition to its well-known influence on the nervous system, it has been associated with gastrointestinal diseases according to numerous authors. Objective: The objective of this study is to gather and analyze literature regarding the associations between vitamin B12 deficiency and gastrointestinal diseases, including gastroesophageal reflux disease (GERD), gastritis, inflammatory bowel disease (IBD), small intestinal bacterial overgrowth (SIBO), and hepatitis C (HCV). Materials and Methods: A literature review was conducted using the PubMed database with the following search terms: vitamin B12, cobalamin, deficiency, gastrointestinal diseases, GERD, IBD, SIBO, HCV. Current Knowledge: Vitamin B12 deficiency can be caused by autoimmune factors, dietary insufficiencies, toxin exposure, and malabsorption disorders related to gastrointestinal diseases. Gastrointestinal conditions such as GERD and IBD can both lead to and be exacerbated by cobalamin deficiency. Furthermore, vitamin B12 deficiency may be worsened by prolonged use of proton pump inhibitors (PPIs) and Helicobacter pylori infection. Conclusions: An adequate amount of vitamin B12 is crucial for gastrointestinal health. Deficiency can significantly impact the course and symptoms of many gastrointestinal diseases. Therefore, monitoring and supplementation of vitamin B12 should be an integral part of managing patients with gastrointestinal conditions.